Cardiovascular risk and attitudes to lifestyle: what do patients think? - Silagy, C (1993)
OBJECTIVE--To examine the relation between subjects' level of cardiovascular risk and their beliefs about the harmfulness of their smoking habit, current diet, and level of exercise, together with their stated desire to modify such behaviour. DESIGN--Self administered postal health and life-style questionnaire followed by a structured health check conducted by a nurse. SETTING--Five general practices in Luton and Dunstable, Bedfordshire. SUBJECTS--5803 people aged 35-64 years enrolled in the OXCHECK trial who attended for a health check before 1 March 1992. MAIN OUTCOME MEASURES--Perceived risk to health of lifestyle behaviours, desire to modify behaviour, and a reported serious attempt to modify behaviour in the preceding year. RESULTS--A high proportion of smokers and those who were physically inactive perceived their behaviour to be harmful (1020; (76%; 95% confidence interval 74% to 79%) and 350 (74%; 70% to 78%) respectively) and wished to modify it (1212 (79%; 77% to 81%) and 375 (74%; 71% to 78%) respectively). In contrast, only 289 (45%; 41% to 48%) of obese people and 188 (14%; 12% to 16%) of people with a high dietary fat intake perceived their current diet to be harmful. The more cardiovascular risk factors present, the more likely subjects were to perceive a health risk attached to their diet and lack of exercise (p < 0.01 in both cases) and to want to improve their diet. CONCLUSION--Awareness of the health risk from smoking and motivation to stop is high. Further efforts are required, however, to educate the public about the risks associated with a high dietary fat intake. Although the health risks of inactivity were widely recognised, motivation to take more exercise needs to be increased.